Hubungan Aktivitas Fisik dengan Kualitas Tidur Pada Mahasiswa Fakultas Kedokteran Universitas HKBP Nommensen - Rajagukguk, Hertaria Yosephine; Ompusunggu, Henny Erina Saurmauli; Zaluchu, Ristarin (Universitas HKBP Nommensen, 2024)
Background: The state of poor sleep is often experienced by everyone, especially among students. Medicine is one of the fields of education with high level of stress because students are required to adapt to various heavy and unsettled academic routines such as class assignments, class changes, breaks, independent study, and other academic activities. There are several ways that can be done to improve the quality of sleep, one of which is by doing physical activity. Objective: This study aims to determine the association between physical activity and sleep quality in students of Medical Faculty, Universitas HKBP Nommensen. Methods: This study was analytic study with a cross-sectional design. The instruments in study were the international physical activity questionnaire (IPAQ) and the Pittsburgh sleep quality index (PSQI). The sample in this study were 104 students from the Medical Faculty of Universitas HKBP Nommensen. The sampling technique in this study used purposive sampling method. Results: In this study, majority of respondents were active 58,7% and had good sleep quality 62,5%. The association between physical activity and sleep quality was analyzed by Chi-Square test and found p = 0,438. Conclusion: There is no relationship between physical activity and sleep quality for students of the Faculty of Medicine, University of HKBP Nommensen. Keywords: Physical activity, sleep quality, Medical